Monteiro Lobato : da obra literária à televisão - Steffen, Lisandra Portela (2008)
This thesis aims to analyzes the overrunning of the main characters of Monteiro Lobato s work, to the O sítio do Picapau Amarelo , television show broadcasted by Rede Globo. In order to do that, four episodes have been analyzed, which were exhibited in 2007. The main goal of this work is to show, how affected is the characters overrunning measures languages features from the writer s work to the television show, from logic of cultural industry. To this purpose, a study and its relevancy to Brazilian children s and juvenile literature about the author live and work is shown. The analyses were based on of Antonio Candido e Benjamin Abdala as regard the construction the characters of fiction. Referring of the overrunning the literature works to the television show, were used the Carlos Straccia, Ana Maria Belog and Vânia Lúcia Quintão theories. Theodor Wisengrund Adorno, Hansmagnus Enzensberger, Pierre Bourdieu e Francisco Rudiger, the communication construction theorists is this thesis base in that matter. Based on those theorist, a characters data cross is donne from the literature work to the following television shows